PENGARUH FINGER PAINTING TERHADAP PERKEMBANGAN MOTORIK HALUS ANAK USIA DINI - Dwi Nomi Pura; Mutia Khoirunnisya Nasution; Anggun Dwi Putri; Dinda Okta Olipia; Ica Imelia (STKIP Subang, 2026)
Finger painting is one of the visual art activities that is effective in developing the fine motor skills of early childhood. This study aims to analyze the influence of finger painting on the improvement of children's fine motor skills, particularly in the aspects of hand-eye coordination, finger flexibility, and movement control. The method used is a literature study by analyzing five empirical research results from scientific journals published in the last 5 years (2021-2025). The analysis results show that finger painting has a significant effect on improving children's fine motor skills, with effectiveness documented statistically. Finger painting activities involve tactile and visual sensory stimulation that supports sensorimotor integration, thereby having a positive impact on hand-eye coordination, grip strength, and children's fine motor control.